Pavement marking materials and markers testing the relationship between retroreflectivity and safety. - Bahar, Geni Brafman (Research results digest (National Cooperative Highway Research Program), 2006)
"This digest summarizes key findings from NCHRP Project 17-28, "Pavement marking materials and markers : safety impact and cost-effectiveness" conducted by iTRANS Consulting, Ltd. The digest is an abridgement of portions of the project final report authored by the principal investigator, Geni Bahar ... [et al.]."